Emotional reinventions : realist-era representations beyond sympathy - Dawson, Melanie, 1967- (University of Michigan Press, 2015)
" Focusing on representational approaches to emotion during the years of American literary realism's dominance and in the works of such authors as Edith Wharton, Alice Dunbar-Nelson, W. D. Howells, Charles Chesnutt, and others, Emotional Reinventions: Realist-Era Representations Beyond Sympathy contends that emotional representations were central to the self-conscious construction of high realism (in the mid-1880s) and to the interrogation of its boundaries. Based on realist-era authors' rejection of "sentimentalism" and its reduction of emotional diversity (a tendency to stress what Karen Sanchez-Eppler has described as sentimental fiction's investment in "overcoming difference"), Melanie Dawson argues that realist-era investments in emotional detail were designed to confront differences of class, gender, race, and circumstance directly. She explores the ways in which representational practices that approximate scientific methods often led away from scientific theories and rejected rigid attempts at creating emotional taxonomies. She argues that ultimately realist-era authors demonstrated a new investment in individuated emotional histories and experiences that sought to honor all affective experiences on their own terms"-- Provided by publisher.
Keywords: American fiction -- 19th century -- History and criticism.; Realism in literature.; Emotions in literature.; Individuality in literature.; Difference (Psychology) in literature.; Roman américain -- 19e siècle -- Histoire et critique.; Réalisme dans la littérature.; Individualité dans la littérature.; LITERARY COLLECTIONS / American / General.; American fiction.; 1800-1899; Criticism, interpretation, etc.